The effect of orange juice against to H2O2 stress in Saccharomyces cerevisiae - Aslan, Abdullah; Can, Muhammed Ismail (Progress in Nutrition, 2015)
In this study, seven groups were composed. i: Control group, ii: H2O2 group, iii: 5 mM H2O2 + orange juice (OJ) group, iv: 10 mM H2O2 + OJ group, v: 15 mM H2O2 + OJ group vi: 20 mM H2O2 + OJ group, vii: 25 mM H2O2 + OJ group. After sterilization, fruit juice (25%) and H2O2 were inserted different concentration to Saccharomyces cerevisiae (S. cerevisiae) cultures and the cultures were developed at 37°C for 1h, 3h, 5h and 24 hours (overnight). S. cerevisiae cell growth was determined by spectrophotometer, total protein alteration was identified by SDS-PAGE electrophoresis and calculated with biuret method. With respect to our studies results; cell growth rised in fruit juice groups to which OJ was taken in proportion to the positive control (H2O2) group at different growing times (1, 3, 5 and 24 hours) (p<0,05). As a result orange fruit juices has a protective role for decrease the oxidative damage and increased cell growing and stimulating protein synthesis in S. cerevisiae.